A Literary Analysis of Love and Liberty in the Poetry ofPercy Bysshe Shelley (Journal of Asian Development Studies, 2024)
This research is a comprehensive literary analysis of the themes of love and liberty portrayed inthe poetry of Percy Bysshe Shelley. Although, beauty, nature, creativity, sanctified imagination,love, liberty and loss are the common celebrated themes of Romantic period, but here we will havea meticulous inquiry into the Shelley's poetic works and will uncover multifaceted nature of loveand liberty as illustrated by this Romantic poet. Furthermore, this research analyzes those ideasand elements which develop the theme of love and liberty. The study is based on qualitative methodof research which incorporates Textual Analysis Method of research. The study conforms totheoretical framework of Romanticism and provide a comprehensive solution to the researchproblem. The framework is developed after reviewing previous literature related to this research.Two types of data are employed in this study; primary data and secondary data. Primary data istaken from five poems of Shelley, while secondary data is collected from online journals, researcharticles and web pages. The selected poems are analyzed through the theoretical framework ofRomanticism. The findings of this research reveal that the themes of love and liberty pervade thepoetry of Shelley. The study aims to provide new vistas to the current scholarly discourse onRomantic poetry. It elucidates Shelley's poetical work that revolves around the undying themes oflove and liberty that enthralls readers across generations. This research is important for itsmeticulous inquiry into the poetry of Shelley to discover the veiled philosophy of love and liberty.It is significant, because it familiarizes the readers about Shelley’s stylistic use of language,imagery and symbolism for better portrayal of meanings.